A condensed-matter analogue of the false vacuum. (11th June 2021) - Gibbons, Mark
Abstract: Through experimental investigation into the behaviour of a polar dielectric working fluid, an ideal 'quasi-thermodynamic' cycle has been established. Particular stages of this cycle are described in terms of a condensed-matter analogue of the false vacuum, when operating under negative pressure. The cycle is established between 37 °C and 15 °C under isochoric conditions. Phase-change work is created in two-directions, positive expansion-work and negative contraction-work. A large proportion of the expansion-work derives from a cooling process where the fluid exhibits negative heat capacity. When heat flux ceases, the fluid becomes unstable and heat capacity switches from negative to positive, displaying a 'non-equivalence of ensembles' phase-change. Whilst elements of the fluid behaviour can only be described by the statistical mechanics of non-equilibrium systems, the calculated equations of state for classical thermodynamics are confirmed to be accurate from the experimental investigation. However, the classical thermodynamic calculations for cycle-efficiency do not produce a symmetry of energy conservation. This suggests that an additional form of energy, having long-range interaction and distinct from heat and work input, is involved in the performance of the quasi-thermodynamic cycle. The expansion of a negative pressure fluid that contains inclusion compounds appears responsible for this potential energy interaction as an analogue of the false vacuum potential that can be explained by application of the virial theorem.